The genotoxicological assessment of a tobacco heating product relative to cigarette smoke using the in vitro micronucleus assay. (2020) - Thorne, David; Whitwell, James; Clements, Julie; Walker, Paul; Breheny, Damien; Gaca, Marianna
Graphical abstract: Highlights: Cigarettes were compared to a tobacco heating product (THP1.0 T) in a comparative study. Traditional and contemporary IVMN approaches were investigated. Multiple cell types and scoring methods were employed. Negative responses were observed for THP1.0 T irrespective of approach. Contemporary approaches proved viable tools for screening purposes. Abstract: In vitro studies have supported the toxicological evaluation of chemicals and complex mixtures including cigarette smoke and novel tobacco and nicotine products which include tobacco heating products (THP). This new environment requires faster testing, higher throughput and appropriate in vitro studies, to support product innovation and development. In this study, total particulate matter (TPM) from a commercially available THP and a reference cigarette (3R4F) were assessed up to 500 μg/mL using two in vitro micronucleus techniques. V79 and TK6 cells were assessed using conventional OECD 487 manual scoring techniques, whereas, CHO cells were assessed using contemporary, automated high content screening approaches (Cellomics ArrayScan® VTI). V79 cells gave the most consistent response with all three treatment conditions producing a clear positive genotoxic response. Human TK6 cells only produced dose-dependent response, indicative of a weak-positive response. CHO cells demonstrated a positive response with TPM using long (24 h) -S9 conditions. All three cell lines equally demonstrated a negative response with THP TPM up to 500 μg/mL. In conclusion, THP TPM did not increase micronuclei formation above control levels even at doses far exceeding that tested with reference cigarette smoke, in most cases up to 10x the dose delivered compared to that of cigarette smoke. This study supports the growing belief that THPs are less risky than conventional cigarettes and that 21st century screening techniques can be employed to support product design and decision making, as a potential 1st screen prior to more traditional assessments.